Development of STEM-Based Learning Media FDS (Fire Detector System) Integrated with Blynk IoT to Improve Students' Creativity on Temperature Material - Erti Hamimi; Dian Nugraheni; Syahrul Candra Ardani; Isnanik Juni Fitriyah; Ikliil Zhaafirahdiningko; Indra Fardhani; Muhammad Fajar Marsuki, (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The Society 5.0 era emphasizes the use of technology and innovation to address social challenges, such as the utilization of Internet of Things (IoT) technology. Creative thinking plays a vital role in generating new ideas and approaches to problem-solving. Science, technology, engineering, and mathematics (STEM)-based education can help individuals develop creative thinking skills by engaging in problem-solving and creating innovative solutions. This study aims to enhance the creative thinking abilities of junior high school students on the topic of temperature through the development of STEM-based instructional media. This is achieved by creating the fire detector system (FDS) educational kit and testing its validity and practicality in the learning process. The study model used in this study is the analysis, design, development, implementation, and evaluation (ADDIE) model. The ADDIE model consists of five stages: analysis, design, development, implementation, and evaluation. The research instruments utilized include structured questionnaires for expert validation and application testing. The participants involved in this study include several seventh-grade students and one science teacher from a junior high school. The collected data is then analyzed using qualitative and quantitative descriptive data analysis techniques. By utilizing the FDS educational kit, it is hoped that it can effectively foster creative thinking skills among junior high school students.